The application and relevance of information and communication technology to architectural education - Oluropo Stephen Ilesanmi; S. C. Folorunso; O. O. Kolade (Program Studi Arsitektur Fakultas Teknik Universitas Katolik Widya Mandira, 2023)
The advancements in Information and Communication Technologies (ICTs) in recent times have made the world to become a global village. This phenomenon has also resulted in global pursuit of improvement in quality of education with access to information and the use of Information and Communication Technology (ICT) becoming important indices for participating in the information age. In like manner, this rapid development in Information and Communication Technology and its applications has introduced new opportunities in architectural education. This paper focuses on the application and relevance of Information and Communication Technology to teaching and learning architecture in Nigeria as a means to squaring up with the global competitiveness in architectural education. It suggests the importance of developing expertise in these applications by architectural educators, so as to carry out and provide creative direction in teaching and learning of architecture. This can bring about improving students’ motivation for active, creative and explorative learning. It concludes with the need for architectural educators in Nigeria, to acquaint themselves with the methods and techniques of application of Information and Communication Technology to teaching and learning of architecture in order to become relevant in this age of globalization.